Research themes in information systems & management research in creative eMedia industries - Lugmayr, Artur (2013)
Within the scope of this paper a basic set of research leads in information systems and management research in creative eMedia industries are investigated to develop the new research area of IS&M in Creative eMedia industries as intersection between research in creative industries, IS&M, and eMedia technologies. The paper revises information systems and management research on general level. This is followed by positioning creative eMedia industries and the development of a suitable categorization model. Particular research areas and themes are identified, and briefly described. The paper closes by discussing the topic matter, and concludes that there is a need for a coherent approach in information system and management research in creative eMedia industries. Copyright © 2010 ACM.